Pola Distribusi Zakat Infak dan Sedekah dalam Mewujudkan Kesejahteraan Sosial : Distribution Patterns of Zakat Infak and Sadaqah in Realizing Social Welfare - Rusmadi Rijal Saleh (ISTIDLAL, 2023)
Allah SWT encourages Muslims to pay zakat and also voluntary funds in the form of infaq and sadaqah. The recipients of zakat to 8 groups of Asnaf that have been determined by sharia, but the recipients of infaq and alms are much broader than zakaah because they can be channeled to anyone in need. This research is a type of library research with a qualitative approach. Data sources are secondary data obtained from library data in the form of journals, research and books relevant to the discussion. Data processing and analysis techniques are carried out by reading, reviewing, and analyzing various existing literature, as well as existing research results then reduced, presenting data until conclusions are obtained. The results showed that various patterns of distribution of zakat, infaq and alms were created by several collecting or receiving institutions by realizing them in various programs. The distribution of ZIS that is carried out in addition to consumptive is also carried out at a productive level. The existence of this distribution pattern has had an impact on its recipients both in the fields of education, health, improving human resources and various other fields.